FOLLICULAR DEVELOPMENT IN POST-PARTUM ANOESTRUS BUFFALOES - KUMAR2, PRAVEEN; BRAMHAIAH K, VEERA; RAO M, MUTHA; GANGARAJU, G (The Indian Journal of Animal Reproduction, 2020)
Pattern of ovarian follicle development and regression was studied in 14 Postpartum Anestrus Buffaloes having>60 days postpartum period. The mean follicles number on both the ovaries was 1.82 ± 0.12 with overall maximumdiameter of 7.50 ± 0.33 mm and the same was 8.07 + 0.48 and 6.97 + 0.45 mm on right and left ovaries, respectively.During this Postpartum Anestrus the period follicular development either stopped or undergone atresia without reachingdominance and ovulation. The mean growth rate of follicles was 0.46 + 0.22 and 0.20 + 0.21 mm per day on right andleft ovaries, respectively with overall growth rate of 0.55 + 0.13 mm per day, while the mean atresia rate was -0.06 +0.35 and -0.80 + 0.17 mm per day on right and left ovaries, respectively with an overall atresia rate of -0.75 + 0.11 mmper day. The correlation co-efficient of follicle diameter with follicle growth rate was positively insignificant (P>0.05)while the same with follicle atresia rate was negatively insignificant (P>0.05).
Keywords: Buffaloes; Post-partum anestrous; follicular development